PRELIMINARY TESTS OF THERMAL CONDUCTIVITY OF SELECTED SOIL TYPES - Ludynia, Agata; Orman, Lukasz J. (European Scientific Journal, ESJ, 2013)
The paper discusses the topic of thermal conductivity investigation of soil. This problem is especially crucial for the design and exploitation of ground heat exchangers. Such systems located in the soil can either extract heat from the ground or transport it there for season storage. Nowadays, these and similar installations are used in connection with renewable energy systems – for example heat pumps. The paper presents the preliminary test results and characteristic properties of selected kinds of soil. Further tests could help to determine the usefulness of different soil types for heat exchanger applications.